Cochlear implantation in irradiated tympanojugular paraganglioma. (2nd December 2015) - Medina, María del Mar; Piccirillo, Enrico; D'orazio, Flavia; Bacciu, Andrea; Guida, Maurizio; Sanna, Mario
Abstract : Objective: Indications for cochlear implantation have extended progressively over the years both from an audiological and clinical point of view, including the introduction of cochlear implants (CI) for hearing rehabilitation following skull base surgeries and neurotological procedures. In the past, cochlear implantation has been used for hearing rehabilitation in radiation-induced sensorineural hearing loss in nasopharyngeal and tonsillar carcinoma with successful outcomes. Here we describe a similar outcome following total deafness after tympanojugular paraganglioma irradiation, which is also the first such report in literature. Design: The irradiated ear of this patient was implanted with a CI through standard posterior tympanotomy. Study sample: A 26 year old male with multiple paragangliomas with bilateral deafness, secondary to surgery on one ear and radiotherapy for the opposite ear. Results: After a follow-up of 48 months, no local complications have occurred and the hearing results have remained stable with 100% sentence recognition. Conclusions: Bilateral and multiple paragangliomas are rare tumors. Despite the modality of treatment, the hearing is almost always compromised. In these patients, cochlear implantation offers a new perspective for hearing restoration. This report demonstrates that cochlear implantation can be effectively performed after tympanojugular paraganglioma irradiation with long-lasting, satisfactory results, even in the presence of residual tumor.